SARS-CoV-2 IN AFRICA, SOCIAL SCIENCE RESEARCH INSTITUTIONS AND BRAIN BOOM - Patrick MBENGUE ZE; Jacques Serge KOUADJOVI KALEDJE II (Analele Universităţii din Craiova. Psihologie, Pedagogie, 2023)
The Coronavirus flu is causing the mobilization of social science research institutions in Africa and leading to unprecedented maieutics. These institutions, in a coordinated way or not, are undertaking convergent reflections on the issues of SARSCoV-2. This pandemic leads scientific sects to reinvent themselves in order to answer to the why/how ? of this epi-pandemic, and to draw the necessary lessons. The burst stimulated by ultra-pessimistic studies on Africa, led to Brain Boom in social sciences. This result through a qualitative approach, contributes to building interdisciplinary bridges, areal studies and exchange platforms, around the issue of safeguarding humanity.